Plasma focus installation as a tool for the study of the interaction of high power plasma streams with condensed matter - Ivanov, L.I.; Dedyurin, A.I.; Borovitskaya, I.V.; Krokhin, O.N.; Nikulin, V.Ya.; Polukhin, S.N.; Tikhomirov, A.A.; Fedotov, A.S. (Вопросы атомной науки и техники, 2002)
In this work the possibilities of the use of the high-current discharges of Plasma Focus type for the investigation of the effect of plasma on the materials are discussed. From this point of view the properties of plasma streams and ion beams arising in the PF discharges are studied. Here, as an example of an application of the Plasma Focus device (PF), we studied the influence on Vanadium (perspective material in nuclear power engineering) a cumulative streams producing in the PF